Counselors’ Role in Addressing Substance Addiction Issues - Gabriel, Melanie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the role of school counselors in addressing substance addiction among students, focusing on commonly used substances, contributing factors, intervention strategies, outcomes, barriers, and a proposed plan of action. Grounded in Bronfenbrenner’s Ecological Systems Theory, the study recognized substance addiction as a concern shaped by individual, family, peer, school, and community influences. A qualitative research design was employed using semi-structured interviews with 10 registered guidance counselors from high schools within the Tarlac City Schools Division and the Division of Tarlac Province. The data were analyzed through thematic analysis. Findings revealed that alcohol and nicotine, particularly vaping or e-cigarette use, were the most commonly used substances among students. Contributing factors included peer pressure, stress, curiosity, self-image, family exposure, easy availability of substances, social media influence, and inadequate coping mechanisms. School counselors addressed these concerns through individual counseling, behavior contracts, follow-up sessions, referrals, peer mentoring, support groups, family engagement, and community collaboration. These interventions contributed to improved self-awareness, healthier coping mechanisms, increased awareness of substance-related risks, stronger peer accountability, and positive emotional and behavioral changes. However, counselors faced barriers such as parental denial, social stigma, limited resources, heavy workload, weak school support, inconsistent policy enforcement, and easy student access to alcohol and nicotine. The study concluded that counselor-led interventions are essential in promoting safer and substance-free school communities. It recommended professional development, awareness campaigns, peer mentorship, regular evaluation of interventions, stronger family participation, community enforcement, and implementation of Project MELANIE. The study supports SDG 3, SDG 4, SDG 16, and SDG 17 by promoting student well-being, quality education, safer institutions, and collaborative prevention efforts. Its sustainability impact lies in strengthening public health, educational, institutional, community, and governance responses to student substance addiction.
Keywords: Alcohol Use; Community Collaboration; Guidance Counselors; Nicotine Use; Peer Mentoring; Project MELANIE; School-Based Intervention; Student Substance Addiction; Thematic Analysis